2022
DOI: 10.34172/mj.2022.023
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a community-based suicide prevention program in primary care

Abstract: Background. Suicide is recognized as a public health issue in Malekan County through a health community assessment. A community-based suicide prevention program was conducted during 2014-2017. Methods. This health system research was conducted in seven steps, including conducting systematic reviews, gathering expert opinions, improving the coverage of suicide attempt records, conducting research to identify regional risk factors, conducting follow ups and managing the individuals attempting suicide, training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The fourth main component of suicide prevention strategies was managing suicide attempters. Azizi et al mentioned that follow-up monitoring of suicide attempters is one of the most effective and efficient strategies to reduce suicide and re-attempt rates in the population of their studies [3,7,15,41]. Findings indicated that the reattempt suicide rate is 16% during the first year of followup, 21% from the second to the fourth year, and 23% after the fourth year [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth main component of suicide prevention strategies was managing suicide attempters. Azizi et al mentioned that follow-up monitoring of suicide attempters is one of the most effective and efficient strategies to reduce suicide and re-attempt rates in the population of their studies [3,7,15,41]. Findings indicated that the reattempt suicide rate is 16% during the first year of followup, 21% from the second to the fourth year, and 23% after the fourth year [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of suicide mortality occurs in low-and middle-income countries, the majority of comprehensive suicide prevention programs have been developed in high-income countries [14]. It is vitally important to encourage and promote the development, implementation, and evaluation of suicide prevention strategies around the world, especially in the PHC settings [15]. Currently, suicide prevention strategies have been developed in medical settings [16].…”
Section: Introductionmentioning
confidence: 99%